KEBIJAKAN KRIMINAL TERHADAP PELAKU TINDAK PIDANA KEPEMILIKAN SENJATA API ILEGAL DALAM WILAYAH HUKUM KEPOLISIAN DAERAH SUMATERA UTARA - Budi Sudarmono, Bonanda Japatani Siregar (YAPEKAM, 2025)
Misuse of firearms is the most common case today, where firearms can cause serious injury or death and one of the most disturbing crimes in society is crime using firearms. From the flow of crime using threats of violence or with firearms, it is indeed very disturbing to the security and order of society, thus causing concern in society. In overcoming criminal acts, it must be a unity by using criminal sanctions, and combined with other efforts that are non-penal. The formulation of this thesis research is as follows: First, how to overcome criminal policies in the crime of misuse of firearms in Indonesia, Second, how to prevent criminal behavior against perpetrators of illegal firearm ownership in the jurisdiction of the North Sumatra Regional Police, Third, how to take action against perpetrators of criminal acts of illegal firearm ownership in the jurisdiction of the North Sumatra Regional Police. The research used is a normative legal research method, namely studying legal principles and analyzing problems, studying and examining through an approach to legal principles and laws and regulations with reference to the 1945 Constitution, Emergency Law Number 12 of 1951 concerning Firearms and Explosives, Government Regulation in Lieu of Law Number 20 of 1960 concerning the Authority of Licensing Granted According to Legislation Concerning Firearms, Regulation of the Chief of Police Number 8 of 2012 concerning Licensing, Supervision and Control of Non-Organic Firearms of the Republic of Indonesia National Police / Indonesian National Army for Sports, Regulation of the Chief of Police Number 18 of 2015 concerning Licensing, Supervision and Control of Non-Organic Firearms of the Republic of Indonesia National Police / Indonesian National Army for Self-Defense.Prevention and Prosecution of criminals in possession of firearms based on Article 1 paragraph (1) of Law Number 12 of 1951 concerning Firearms and Sharp Weapons, has expressly regulated the prohibition of possessing and carrying firearms or explosives. Thus, possessing a firearm without a permit is one type of criminal act in Indonesia. In addition, its use is a threat to security and order in society, because it can be misused such as to commit crimes of robbery, kidnapping and so on. Finally, it can be stated that possession of a firearm without a permit is categorized as a criminal act, not only after committing an act of using the firearm against another person, but carrying a firearm or hiding it is already a criminal act.